South Africa Economic Update, November 2011 : Focus on Green Growth - World Bank (Washington, DC, 2017)
The global financial roller coaster, with the Euro zone as its lead car, has hit economic prospects across the globe. The South African economy, with its close links to the world economy, has suffered, too, resulting in weakened growth prospects, lower fiscal revenues, lower and more volatile valuation of the rand, and dampened external financing. This further compounds the policy challenges facing the authorities, on top of their preoccupation with unyielding unemployment, which requires higher and more inclusive economic growth. Policymaking is also conditioned by a growing recognition that future growth needs to be less carbon-intensive. As elsewhere, opportunities in green economies are viewed with keen interest, as a way of simultaneously targeting a cleaner environment and stimulating innovation, growth, and job creation. While green policies can have large synergies and co-benefits with the growth and employment agenda, they are not a substitute for it. Indeed, such synergies are likely to be mutually enhancing and larger when the growth and environment objectives are being pursued by multiple, well-targeted and coordinated policies.